The need for sharps boxes to be offered in the hospital setting for people who use substances: Removing sharps boxes puts all of us at risk - Forchuk, Cheryl; Silverman, Michael; Rudnick, Abraham; Serrato, Jonathan; Schmitt, Brenna; Scott, Leanne (Frontiers in Health Services, 2023)
Introduction Substance use can occur in the hospital setting among people with substance use disorder, including intravenous use. However, the provision of sharps boxes is not typically offered in Canadian hospitals. This study set out to explore the current issues due to the lack of harm reduction in the hospital setting. Method Thirty-one health care professionals participated in virtual one-to-one interviews and focus groups regarding harm reduction in hospital. The issue of sharps box removal was highlighted as a concern. A secondary ethnographic thematic analysis explored this theme in more detail. A scoping review of the literature observed additional considerations. Findings Sharps box removal was commonplace for people who were known to be, or suspected of, using substances. Sharps boxes only to be used for medical purposes and fears of box tampering were cited as reasons for removal. Health care professionals noted that patients would have to use sharps boxes situated elsewhere. The scoping review revealed that needlestick injuries for hospital staff decreased with greater access to sharps boxes in hospital. Injuries can be addressed through safer disposal practices. Modern designs of sharps boxes and educational initiatives have been found to be successful in sharps disposal compliance and reductions in related injuries. Discussion Ensuring equitable access to sharps boxes would help to reduce unsafe needle discarding which can lead to needlestick injuries for hospital staff and potentially other patients. Education would be a key step in furthering understandings of the importance of sharps boxes and harm reduction as a whole.